Strategic planning to prevent spread of maize Lethal Necrosis - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
To raise awareness about the status of maize lethal necrosis (MLN) spread and progress towards MLN control in MLNA-affected regions in East Africa. To discuss and prioritize action plans for preventive control of MLN